Любовь, как дар Бога и как смысл и часть души и сознания - Фидровская, Мария Георгиевна (Society for Cultural and Scientific Progress in Central and Eastern Europe, 2018)
В данной статье рассматривается феномен любви и его проблемность для современного общества. Здесь будут рассмотрены четыре вида любви в соответствии с делением Платона и будет в соответствии с каждым выведено то место, которое этот вид занимает в современном обществе. Более того, мы посмотрим с какими проблемами в отношении любви мы сегодня сталкиваемся в обществе и философии.

In the following article it is considered the phenomena of love and its problem for modern society.Here we will consider four kinds of love according to the division of Plato and according to each one we will find its place in modern society. Moreover, we will see the problems about love we meet in modern society and philosophy.
Love as a gift of God and as a sence and part of the soul and of the consciousness
Keywords: агапе; христианство; общество; телос; agape; Christianity; society; modern